Conformational adaptability determining antibody recognition to distomer: structure analysis of enantioselective antibody against chiral drug gatifloxacin. Issue 62 (13th December 2021) - Wang, Lanteng; Xie, Wei; Jiao, Wenyang; Zhang, Chijian; Li, Xiangmei; Xu, Zhenlin; Huang, Xin-an; Lei, Hongtao; Shen, Xing
Abstract : The conformational adaptability of both antibody and ligand could determine the antibody enantioselectivity in chiral drug immunoassay. Abstract : Enantioselective antibodies have great potential to separate and detect chiral compounds. However, cross-reactivity of enantioselective antibodies to the distomer may limit the application. An in-depth understanding of interactions between antibodies and chiral drugs could be helpful to investigate antibody recognition to the distomer. In this study, a monoclonal antibody against chiral quinolone S -(−)-gatifloxacin ( S -GAT) was produced and its Fab fragment was prepared by proteolysis. The S -GAT Fab exhibited 10% cross-reactivity against the R -enantiomer compared to that of the S -enantiomer in an indirect competitive enzyme-linked immunosorbent assay (icELISA). The crystal structures of the S -GAT Fab apo form and complex with S -GAT were analyzed, and molecular docking of the R -enantiomer was carried out. The ligand conformation was further studied using molecular dynamics simulations. The results showed that the distomer R -enantiomer could enter the chiral center recognition region of the antibody by adjusting the piperazine ring conformation. Meanwhile, the antibody binding cavity had obvious conformational adaptability during ligand binding. It demonstrated that conformational change of both ligand and antibody was the key reason why antibodies recognize the distomer. Restricting conformational adaptability could improve the enantioselective recognition ability of antibodies. This study provided a new explanation for the cross-reactivity of enantioselective antibodies to the distomer, and could help to modulate antibody enantioselectivity for immunoassay of chiral drugs.